The Student Dermatology Clinic for the Underserved: A Service-Learning Model to Promote Skin Health Equity - Patel, Bansri M.; Humphrey, Victoria; James, Alaina J. (International Journal of Medical Students, 2022)
People who are uninsured and live in underserved communities face several barriers to accessing dermatologic care, including financial, geographic, and racial barriers, resulting in detrimental effects on health outcomes and quality of life. We (1) describe and evaluate an innovative, student-faculty run dermatology free clinic that serves people in marginalized populations and (2) present action steps to strategically develop community partnerships and integrate a service-learning program into a dermatology residency training program for medical students and residents. The Student Dermatology Clinic for the Underserved (SDU) is a quarterly, student-faculty run free clinic at a community health center in Pittsburgh that serves the marginalized populations within our community. Interprofessional teams of medical students and dermatology residents evaluate patients, devise patient care plans with the dermatology attending physician, and coordinate follow-up care. In a survey of residents who voluntarily participated in SDU, 88% (n=8) report that their involvement increased their awareness of health disparities and social factors impacting dermatologic care and encouraged them to be more involved in community service throughout their career. The SDU clinic is an instrumental resource in our community that allows for patient-centered, longitudinal care, while reducing barriers to access for patients in underserved communities. In this service-learning model for dermatology residency training programs, we not only address the dermatologic needs of marginalized populations, but we also create a rewarding training environment for medical students and residents that facilitates vertical learning and interprofessional collaboration, fosters an interest in health disparities, increases skin health equity, and cultivates cultural sensitivity.